Determination of endrin and δ-keto endrin in five food products of animal origin using GC-μECD: A modified QuEChERS approach to traditional detection. (15th October 2018) - Rahman, Md. Musfiqur; Lee, Han Sol; Abd El-Aty, A.M.; Kabir, Md. Humayun; Chung, Hyung Suk; Park, Jong-Hyouk; Kim, Mi-Ra; Kim, Ji-hyun; Shin, Ho-Chul; Shin, Sung Shik; Shim, Jae-Han
Graphical abstract: Highlights: A method was developed for detection of endrin and δ-keto endrin in fatty food matrices. The QuEChERS method was modified for GC-μECD traditional detection. A double layer carbon/PSA-SPE cartridge was used for removal of fatty matrix. Because of matrix effect, a matrix-matched calibration was prepared for data analysis. Standards were confirmed via mass spectrometry, and the overall method was further validated through inter-laboratory analysis. Abstract: A simple quick, easy, cheap, effective, rugged, and safe (QuEChERS)-based method was developed for the analysis of endrin and its metabolite, δ-keto endrin, in five animal-derived food products (chicken, pork, beef, egg, and milk) using a gas chromatography-micro electron capture detector (GC-μECD). Samples were extracted with acidified acetonitrile, salted out with magnesium sulfate and sodium acetate, and finally purified with a dual layer solid-phase extraction cartridge (SPE) that contains both Supelclean ENVI-Carb (upper layer) and primary secondary amine (lower layer) SPE sorbents. A seven-point external calibration curve was constructed both for the solvent and matrix for both compounds. Good linearity was achieved for both analytes, with coefficients of determination ( R 2 ) ≥ 0.9960. The limits of detection (LODs) were 0.003 mg/kg, whereas the limits of quantification (LOQ) were 0.01 mg/kg, which were 10 times lower than the extraneous maximum residue limit (EMRL) designated by CODEX Alimentarius for the specified matrices. The method was validated via recovery performances in triplicates, with three fortification levels equivalent to LOQ, 2 × LOQ, and 10 × LOQ. The method provided excellent recoveries, ranging between 75.63 and 117.92%, with relative standard deviations (RSD) ≤ 8.52% for both analytes in various matrices. The developed method was successfully applied to monitor market samples collected from 20 different places throughout the Republic of Korea, and none of the tested analytes were found in the analyzed samples. Conclusively, we could propose that the current method can be used for routine analysis of endrin and δ-keto endrin in any type of fatty food matrix.